STUDY OF Coleus amboinicus STEM EXTRACT IN INHIBITING MACROPHAGE CD-68 EXPRESSION IN WISTAR RATS WITH URIC ACID-INDUCED NEPHROPATHY - Solfaine, Rondius; Mubarokah, Wida Wahidah; Muniroh, Lailatul (Jurnal Kedokteran Hewan, 2019)
The purpose of this study was to evaluate effect of Coleus amboinicus (CA) stem extracts on uric acid-induced nephropathy by comparingthe levels of Macrophage CD-68 expression and concentration of serum Cystatine C (CYS C ) in Wistar rats. Twenty-four male Wistar rats(Rattus norvegicus) with a body weight (bw) of 200-250 g, were allocated into three groups, with eight animals per group. The rats in controlgroup (PO) received 0.1% carboxymethyl cellulose (CMC) solution orally The rats in group 2 (P1) were orally induced with uric acid (UA) (500mg/kg) and oxonic acid (OA) (750 mg/kg.) and the rats in group 3 (P2) received uric acid (500 mg/kg), oxonic acid (750 mg/kg), and 500 mg/kgof the CA stem extracts for 35 days. Bloods were collected for analysis of serum CYS C expression and concentration of serum creatinine andblood nitrogen urea (BUN). The rats in all groups were sacrificed for kidney tissue extractions for macrophage CD-68 identification andhistopathology analysis. The levels of CYS C concentrations were analyzed by Avidin-Horseradish Peroxidase (HRP) Sandwich-ELISA. Theresults showed that Coleus amboinicus stem extract at dose of 500 mg/kg bw can significantly reduce BUN and creatinine levels (P0.05), whileCys C levels were not different. In the treatment group (P2) compared with group (P1). CD-68 (ED-1) macrophage activity decreasedsignificantly (P0.05) in the treatment group (P2) compared to the control group and (P1). Nephrophaty induction using UA and OA causessevere kidney lesions characterized by degeneration, necrosis and inflammation of the renal tubules and glomerulus in the treatment group.